PELATIHAN PASCAPANEN TALAS (Colocasia esculenta) MENJADI TEPUNG GLUTEN-FREE: PEMBERDAYAAN PKK DESA LALONONA, KABUPATEN KONAWE - Maretik, Maretik; Yanti, Yanti; Kharisma, Gaby Nanda; Mehora, Sutrisnawati; Ernawati, Ernawati; Astuti, Widia; Rifqi, Rifqi; Fandri, Fandri; Maulia, Tri Putri (Jurnal Abdi Insani, 2025)
Lalonona Village is a village in Amonggedo District, Konawe Regency, Southeast Sulawesi Province. One of the sectors that is a source of life for the community to meet their daily needs is the agricultural sector, one of which is taro. The main problem for the community is that they find it difficult to handle taro if it is not sold out in the market, so the remaining taro is just stored until it becomes moldy and rots. The purpose of this PKM activity is to improve the knowledge and skills of partners in post-harvest processing of taro and packaging as well as offline or online marketing training. The activity was carried out through five stages: the preparation stage, the socialization stage, the training stage, the mentoring stage and evaluation. The results obtained prove that there is an increase in partner knowledge after the PKM activity. This is according to the results of the community post-test after participating in the PKM activity, community knowledge and skills increased by 100%. At the level of community empowerment in the production sector, the pre-test results were 10-20% and in the post-test increased by 100%, and at the level of community empowerment in the marketing sector, the pre-test results were 20% and in the post-test increased by 100%. Following the Community Service Program (PKM) implementation, it was clear that all activities were carried out according to plan and successfully enhanced the knowledge and skills of the partners. The Lalonona Village Family Welfare Movement (PKK) group was very enthusiastic in participating and directly involved in the entire series of PKM activities. The results of the PKM implementation revealed an increase in community knowledge and skills regarding post-harvest processing of taro into gluten-free taro flour.